Analisis Manajemen Penyelenggaraan Majelis Taklim: Studi Kasus Majelis Taklim Raudhatul Jannah Cengkareng Jakarta Barat - Azzahro, Fatimah; Salamah, Hartini; Ali, Ahmad Jum'a Khatib Nur (ISLAMIKA, 2024)
Majelis taklim is a non-formal institution recognized by the government. The existence of majelis taklim serves as one of the pillars in the development of Islamic education in society. The crucial role of majelis taklim certainly requires good management of its implementation. Therefore, this research aims to determine the management of Islamic education implementation in majelis taklim. This research uses majelis taklim Raudhatul Jannah in Kapuk, West Jakarta as its subject. The research method used is descriptive qualitative. The research instruments used are interviews and observations. The main respondent is the administrator of majelis taklim Raudhatul Jannah, with observation conducted for two months. The analysis conducted using the interactive model bya Miles and Huberman. The results show that the majelis taklim has fulfilled the elements and provisions stipulated in the Ministry of Religion Affairs Regulation number 29 of 2019. The management of administration uses on operational model. The teacher possesses adequate competencies in sufficient numbers. Activities take place not only mosque but also in classrooms and the homes of administrators and mentors. The teaching material focuses on learning the Qur’an with tajwid, recitation, and interpretation methods. Meanwhile, other materials use lectures, question and answer sessions, and practice with exercises for specific topic. This research finds that, in accordance with the standards set by the Ministry of Religious Affairs, the management of majelis taklim implementation can be categorized as well-managed.